ANALISIS PELATIHAN DAN PENGEMBANGAN KARYAWAN PERUSAHAAN RETAIL - Oktaviyani, Alldila; Amborowati, Agustin (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Human resources are one of the factors that play a direct role in carrying out company activities. Training and development also aim to improve performance, efficiency both energy and time and as a means to increase knowledge for employees (Ridwan & Hardianti, 2019). This study aims to determine the implementation of employee training and development in Luwes Gading Surakarta. The research design used is a case study that discusses employee training and development activities with a descriptive discussion method. The object of this study is Luwes Gading Surakarta. The data collection method is carried out by making observations (observations), case studies from previous data and research to conducting in-depth interviews with the object of study. The results of the research can be seen that the implementation of employee training and development in Luwes Gading has been carried out. It can be seen from the existence of basic mentality training programs, capacity building training and on the job training. Meanwhile, the existing development programs in Luwes Gading include promotion, rotation of positions, and the application of the use of new technology as a result of changes in the business environment. Planning of training and development activities can be carried out using the Training Needs Analisys (TNA) method.